Anatomical Study on Meckel Cave with Endoscopic Endonasal, Endo-Maxillary Sinus, and Endo-Pterygoid Process Approaches - Wang, Xuejian (Public Library of Science, 2014)
OBJECTIVE: To study anatomical structures related to Meckel cave with endonasal endoscopic approach and to provide an anatomical basis for endoscopic surgery in Meckel cave. METHODS: Meckel cave of 5 adult skulls (10 sides) were fixed with 10% formalin. The anatomical structures of Meckel cave and the related zones adjacent to Meckel cave were observed and measured with endoscopic endonasal approach. RESULTS: Endoscopic endonasal, endo-maxillary sinus, and endo-pterygoid process approaches were successfully applied in observation of the anatomical structures of meckel cave and the rerated zones adjacent to Meckel cave and in measurement of distances between related anatomical structures for each case of samples. The relevant data were obtained. The distance between the front mouth of palatovaginal canal and vidian canal was 21.4±7 mm, the distance between opening of sphenoid sinus to the upper margin of the choana was 22.3±2.8 mm, the distance between the opening of vidian and foramen rotundum was 7.57±0.7 mm and the length of the pterygoid canal was 13.3±1.2 mm. Based on these data, the positions of the related important structures can be roughly located during surgical operation and various important structures in Meckel cave and its adjacent zones can be found out in a convenient and safe way. CONCLUSION: 1) It is feasible to use endonasal endoscopic approach to perform surgical operation in Meckel cave; 2) Use of endonasal endoscopic approach can protect and fully take the advantage of the vidian nerve to locate the position of foramina lacerum of the internal carotid artery during surgical operation; and 3) the observational and experimental data obtained with this approach can provide the rational basis for clinical operation procedures.